Β-Catenin-Independent Roles of Wnt/LRP6 Signaling. Issue 12 (December 2016) - Acebron, Sergio P.; Niehrs, Christof
Abstract : Wnt/LRP6 signaling is best known for the β-catenin-dependent regulation of target genes. However, pathway branches have recently emerged, including Wnt/STOP signaling, which act independently of β-catenin and transcription. We review here the molecular mechanisms underlying β-catenin-independent Wnt/LRP6 signaling cascades and their implications for cell biology, development, and physiology. Trends: Wnt/LRP6 signaling is thought to proceed by β-catenin mediated transcription. However, this pathway branches off to trigger a variety of other processes, revising the traditional transcription-centric view. Wnt/STOP signaling is one such novel branch of Wnt/LRP6 signaling, which peaks during mitosis to slow down protein degradation as cells prepare to divide. Transcription-independent Wnt/LRP6 signaling regulates cell growth and mitotic progression in dividing cells, axonal remodeling in post-mitotic neurons, and maturation of germ cells.